Performance Characterization of a Vanadium Redox Flow Battery at Different Operating Parameters under a Standardized Test-Bed System - Mohd Rusllim, Mohamed; P. K., Leung; M. H., Sulaiman (Elsevier, 2015)
This paper describes the experimental characterization of a 25 cm2 laboratory scale vanadium redox flow battery (V-RFB). The unit cell performance with respect to voltage, coulombic and energy efficiencies under different performance parameters (current densities, operating temperatures, flow rates, electrolyte concentrations and material properties of 5 cm × 5 cm electrodes) are presented. The cell exhibits different characteristics under different operating parameters; the highest energy efficiency is recorded at c.a. 82%, operating at 308 K, 60 mA cm−2 and 3 cm3 s−1 volumetric flow rate for 250 cm3 electrolytes (each reservoir) of 1.6 mol dm−3V(III)/V(IV) in 4 mol dm−3 H2SO4. Formation charge of the mixture of vanadium species into single electro-active species at positive and negative electrodes are presented. Estimated time for the electro-active species to complete the formation charge using electrochemical calculation of Faraday’s constant are presented; a discrepancy of 4.5% is found between the theoretical and experimental data using current density of 80 mA cm−2.